Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/(sici)1097-4652(199611)169:2<235::aid-jcp2>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive secretion of β‐trace protein by cultivated porcine choroid plexus epithelial cells: Elucidation of its complete amino acid and cDNA sequences

Abstract: Primary porcine choroid plexus epithelial cells cultivated in chemically defined medium maintain their epithelial characteristics and form confluent monolayers. They produce a fluid the composition of which resembles cerebrospinal fluid. The present study demonstrates constitutive secretion of large amounts of beta-trace protein. This intrathecally synthesized protein is a prominent polypeptide constituent of natural cerebrospinal fluid. According to the identity of amino acid sequences it has previously been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…As beta-trace is found in high concentrations in human CSF and since it lacks a signal peptide (Zahn et al, 1993), in situ hybridization and immunocytochemical staining lend support to the idea that beta-trace is synthesized and secreted in the human CNS by the epithelial layer of the choroid plexus (Blödorn et al, 1996). This hypothesis is further supported by the results obtained by Hoffmann et al (1996b) who demonstrated that cultured epithelial cells of porcine choroid plexus constitutively secrete beta-trace.…”
Section: Discussionmentioning
confidence: 57%
“…As beta-trace is found in high concentrations in human CSF and since it lacks a signal peptide (Zahn et al, 1993), in situ hybridization and immunocytochemical staining lend support to the idea that beta-trace is synthesized and secreted in the human CNS by the epithelial layer of the choroid plexus (Blödorn et al, 1996). This hypothesis is further supported by the results obtained by Hoffmann et al (1996b) who demonstrated that cultured epithelial cells of porcine choroid plexus constitutively secrete beta-trace.…”
Section: Discussionmentioning
confidence: 57%
“…24 This supports the currently held concept that in addition to producing CSF, the ChPCs have an endocrine function because they produce an insulin-like growth factor II 19 and calcyphosine. 9 Also, the ChPCs produce several active substances, among which are the transport protein transthyretin, 23 a ganglioside GD3, 12 a prostaglandin-D synthase (''beta-trace protein''), 11 and a retinaldehyde dehydrogenase. 26 Recently, synaptophysin has been found to be present in both normal and neoplastic ChPCs.…”
Section: Discussionmentioning
confidence: 99%